EKSISTENSI SUFISME DALAM TRADISI PEDAQ API DI LOMBOK - Zuhriah, Nur Zuhriah Azizah (HUMANIKA, 2019)
Abstract This study discusses the existence of Sufism in the tradition of the pedaq api in Lombok. Pedaq api as a naming procession cannot be interpreted visually, but is a 'text' culture that is full of meaning and represented by symbolic signs. The elements that exist in the pedaq api imply the essence of the human self itself, because it is motivated by philosophical thinking that interprets the elements of human life. The analysis used is the semiotic Roland Barthes methodology. From this study three concepts of the existence of sufism were obtained in the tradition of the pedaq api. First, the tradition of pedaq api as salvation. Second, the tradition of the pedaq api as an intermediary to remind the agreement of the child with his God. Third, the tradition of pedaq api as a representation of the journey of human life from the beginning of the incident to death.Â